Experimental study and analytical modeling on tensile performance of basalt textile reinforced concrete. (18th January 2021) - Liu, Sai; Wang, Xuan; Rawat, Prashant; Chen, Zheng; Shi, Caijun; Zhu, Deju
Highlights: BTRCs offer a pseudo-ductile behavior under uniaxial tensile loading resulting in multiple microcracks on matrix. The tensile strength, strain, and energy absorbed of BTRC-6 are improved by factors of 2.5, 5.25, and 14.51, respectively, as compared to reference samples. The characterization technique DIC can determine step-by-step crack-formation in three, four, and six-layered BTRCs samples. ACK and CEB analytical models were used to predict the tensile stress–strain behaviors of BTRCs samples. SEM observations of fracture surface showed that with the increase in textile volume fraction in BTRCs result improvement in the crack-bridging mechanism. Abstract: This study investigates the influence of textile layers on the uniaxial tensile performance of the basalt textile reinforced concretes (BTRCs). The tensile tests were conducted on BTRCs reinforced by three, four and six numbers of basalt textile layers. It was found that the textile reinforcement would enhance the tensile strength, ultimate strain, and total energy absorption of the BTRCs, but also reduced the first crack stress and strain of the cement matrix. Meanwhile, the formation of lateral cracks, debonding and textile pull-out phenomenon can be observed by Digital Image Correlation (DIC) and Scanning Electronic Microscopy (SEM), respectively. The predicted stress–strain relationships by the ACK model are higher and lower than that obtained from the CEB model in the pre- and post-cracking ranges, respectively. Moreover, The Aveston-Cooper-Kelly (ACK) and Comite Euro-International Du Betom (CEB) analytical models were used to predict the tensile stress–strain behaviors in BTRCs. The experimentally measured stress–strain relationships for BTRC can be almost enveloped in the area bordered by the CEB and ACK predicted curves.